The value of 68Gallium‐DOTATATE PET/CT in sinonasal neuroendocrine tumor management: A case series. Issue 6 (31st March 2021) - Liu, Katherine Y.; Goldrich, David Y.; Ninan, Sen J.; Filimonov, Andrey; Lam, Hansen; Govindaraj, Satish; Iloreta, Alfred Marc
Abstract: Background: 68 Gallium‐DOTATATE ( 68 Ga‐DOTATATE) is a somatostatin analog used as a PET tracer to successfully identify neuroendocrine tumors (NETs). Due to the rarity of sinonasal NETs, there are few recommendations for 68 Ga‐DOTATATE imaging in these patients. Methods: We discussed the impact of 68 Ga‐DOTATATE imaging on the management of six sinonasal NET cases and reviewed existing literature. Results: 68 Ga‐DOTATATE PET/CT revealed an unknown primary in one case and identified metastatic disease in a primary sinonasal small cell neuroendocrine carcinoma (SNEC) patient missed on conventional imaging. In two esthesioneuroblastoma (ENB) patients, 68 Ga‐DOTATATE detected abnormal radiotracer uptake not present on 18F‐FDG PET/CT and identified a patient for treatment with 177 Lu‐DOTATATE. Conclusions: This is the one of the first few reports, and the largest series to our knowledge, demonstrating the utility of 68 Ga‐DOTATATE imaging for primary sinonasal SNEC and ENB. Further study is required to determine its role in sinonasal NET management.